Kompromi Islam dan Adat pada Praktik Keagamaan Muslim Bugis di Sulawesi Selatan - Jubba, Hasse; Rustan, Ahmad Sultra; Juhansar, Juhansar (JSW (Jurnal Sosiologi Walisongo), 2018)
This article explores the form of compromise between Islam and local tradition (adat) in the religious practices of Muslims in Bugis community in South Sulawesi. Islam is an integral part of Bugis lives and is positioned as the main reference so that it encourages Bugis community members to become more fanatic than others. However, in some cases, it is not uncommon for religious practices that have traditional nuances. In fact, the local tradition is in a position that exceeds the role of religion as reflected in the celebration of Islamic holidays. This condition allows the attraction between religion and local tradition to occur in the practice of everyday life of the Bugis community. The question is at what level do conflicts and compromises occur between local tradition and religion among the Bugis community? To answer this question, an investigation was carried out using qualitative methods that put forward and applying the techniques of participant observation and literature study. The results show that points of compromise were discovered where religion and local tradition complemented each other. The tendency to compromise Islam and local tradition is motivated by not only the low understanding of religion itself but also the desire to maintain the ancestral local traditions that have been practiced for a long time in their community. The compromise of Islam and local tradition in religious practices have resulted in the escape of their respective positions, and it makes the role of religion tends to weaken.